DAMPAK SYDNEY SWEENEY DAN E-WOM TERHADAP NIAT BELI AMERICAN EAGLE: PERAN MEDIASI CITRA MEREK DI DKI JAKARTA - Veronica Sjarifudin Sjarifudin (SIMPLEX: Journal of Economic Management, 2026)
This study aims to understand how brand ambassadors and electronic word of mouth(eWOM) shape consumers’ purchase intention, with brand image positioned as the mediating variable. The research focuses on American Eagle consumers in the DKI Jakarta area who are familiar with the marketing campaign featuring Sydney Sweeney as the brand ambassador. A quantitative approach was employed, using purposive sampling to collect data from 233 qualified participants. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method through the SmartPLS 4.0 software. The findings reveal that both brand ambassadors and eWOM make a positive and significant contribution to brand image as well as purchase intention. Additionally, brand image is shown to act as a partial mediator in the relationship between the independent variables and purchase intention. Overall, the results highlight that leveraging public figures and digital communication serves as an important strategy for strengthening brand perception and encouraging consumer purchase intention.